2008
DOI: 10.1121/1.2836763
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the invariance principle for active sonar

Abstract: Active sonar systems can provide good target detection potential but are limited in shallow water environments by the high level of reverberation produced by the interaction between the acoustic signal and the ocean bottom. The nature of the reverberation is highly variable and depends critically on the ocean and seabed properties, which are typically poorly known. This has motivated interest in techniques that are invariant to the environment. In passive sonar, a scalar parameter termed the waveguide invarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 12 publications
(7 reference statements)
1
28
0
Order By: Relevance
“…Using / ¼ 52 and / 0 ¼ 20 in Eq. (18) yields a value for the waveguide invariant b ¼ 1.3, a value consistent with experimental results 3,4 when both source and receiver are below the main thermocline.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Using / ¼ 52 and / 0 ¼ 20 in Eq. (18) yields a value for the waveguide invariant b ¼ 1.3, a value consistent with experimental results 3,4 when both source and receiver are below the main thermocline.…”
Section: Introductionsupporting
confidence: 70%
“…The canonical value in shallow water is b ¼ 1, but this choice may prove far too coarse. If both the source and array are below the thermocline, both simulations 2 and experiments 3,4 have shown that b ¼ 1.3 or 1.4 is more appropriate. Erroneously assuming b ¼ 1 when it is actually b ¼ 1.3 translates directly into a 30% error in the estimated value for the range.…”
Section: Introductionmentioning
confidence: 99%
“…In most shallow water environments, b is roughly constant with a value close to 1. The apparent simplicity of the WI gave rise to an exhaustive set of applications (passive localization, 9,10 geo-acoustics inversion, 11 active sonar, 12,13 source separation, 14 dispersion compensation 15,16 ). On the other hand, Baggeroer 17 and Rouseff and Spindel 18 simultaneously reminded that considering the WI as a constant is not realistic for stratified SSPs, where refraction becomes non-negligible.…”
Section: Introductionmentioning
confidence: 99%
“…This idea is mentioned in several papers 3,4,12 but it has never been introduce directly in a derivation of E b . Second, we derive the WI from Eq.…”
mentioning
confidence: 99%
“…The waveguide invariant has been used for a wide range of applications such as: passive range estimation [58,56,62], matched field processing [59,23], active sonar [49,27,25], array processing [37,57,66], time-reversal mirrors [32,54,38,39], and more (See Appendix A for a complete review of the waveguide invari-ant literature). Despite its many uses, the waveguide invariant is not well studied compared to other ocean-acoustic phenomena.…”
Section: Introductionmentioning
confidence: 99%